Optimizing the design and dosing of dry powder inhaler formulations of the cationic liposome adjuvant CAF®01 for pulmonary immunization - Thakur, Aneesh; Xu, You; Cano-Garcia, Guillermo; Feng, Siqi; Rose, Fabrice; Gerde, Per; Andersen, Peter; Christensen, Dennis; Foged, Camilla (Frontiers in Drug Delivery, 2022)
Thermostability is one of the product characteristics preferred by WHO for vaccines against respiratory infections due to ease of administration, pain minimization, and low costs. Thermostable dry powder inhaler (DPI) vaccine formulations can induce protective antibodies and T cells at the site of infection in the lungs. However, the majority of licensed human vaccines is based on liquid dosage forms, and there is no licensed mucosal adjuvants. The cationic adjuvant formulation 01 (CAF®01) is a liposome-based adjuvant system that (i) induces robust T cells and antibodies, (ii) is safe and well-tolerated in clinical trials, and (iii) induces mucosal immune responses after pulmonary administration. However, the optimal DPI formulations of CAF®01 for pulmonary immunization are not known. Here, we show that DPI formulations of CAF®01 spray-dried with a combination of sugars and the amino acid leucine exhibit optimal aerosolization properties and distribute in the lung lobes upon pulmonary administration. We demonstrate that the type of amorphous sugar used as stabilizer and the amount (w/w) of leucine used during spray drying affect the physicochemical properties and aerosol performance of DPI formulations. By systematically varying the ratios (w/w) of trehalose, dextran and leucine used as excipients during spray drying, we manufactured DPI formulations of CAF®01 that displayed (i) a spherical or wrinkled surface morphology, (ii) an aerodynamic diameter and particle size distribution optimal for deep lung deposition, and (iii) solid-state and aerosolization properties suitable for lung delivery. Using a design-of-experiments-based approach, we identified the most optimal process parameters in an in vivo aerosol generator, i.e., the PreciseInhale® system, which was used to measure the flowability of the aerosols. We found that the DPI formulation of CAF®01 spray-dried with trehalose and dextran (70% w/w) and leucine (30% w/w) displayed the most optimal physicochemical, morphological, solid-state, and aerosolization properties for deep lung deposition. Upon pulmonary administration, this DPI formulation distributed in the lung lobes in a way that was almost identical to the biodistribution of the non-spray dried formulation. Hence, DPI formulations of CAF®01, prepared with trehalose and dextran sugar matrix and a leucine shell, display physicochemical and aerosol properties suitable for inhalation.